Influence of Different Electron Donors and Acceptors on Dehalorespiration of Tetrachloroethene by Desulfitobacterium frappieri TCE1 - Gerritse, Jan (American Society for Microbiology, 1999)
Strain TCE1, a strictly anaerobic bacterium that can grow by reductive dechlorination of tetrachloroethene (PCE) and trichloroethene (TCE), was isolated by selective enrichment from a PCE-dechlorinating chemostat mixed culture. Strain TCE1 is a gram-positive, motile, curved rod-shaped organism that is 2 to 4 by 0.6 to 0.8 μm and has approximately six lateral flagella. The pH and temperature optima for growth are 7.2 and 35°C, respectively. On the basis of a comparative 16S rRNA sequence analysis, this bacterium was identified as a new strain of Desulfitobacterium frappieri, because it exhibited 99.7% relatedness to the D. frappieri type strain, strain PCP-1. Growth with H(2), formate, l-lactate, butyrate, crotonate, or ethanol as the electron donor depends on the availability of an external electron acceptor. Pyruvate and serine can also be used fermentatively. Electron donors (except formate and H(2)) are oxidized to acetate and CO(2). When l-lactate is the growth substrate, strain TCE1 can use the following electron acceptors: PCE and TCE (to produce cis-1,2-dichloroethene), sulfite and thiosulfate (to produce sulfide), nitrate (to produce nitrite), and fumarate (to produce succinate). Strain TCE1 is not able to reductively dechlorinate 3-chloro-4-hydroxyphenylacetate. The growth yields of the newly isolated bacterium when PCE is the electron acceptor are similar to those obtained for other dehalorespiring anaerobes (e.g., Desulfitobacterium sp. strain PCE1 and Desulfitobacterium hafniense) and the maximum specific reductive dechlorination rates are 4 to 16 times higher (up to 1.4 μmol of chloride released · min(−1) · mg of protein(−1)). Dechlorination of PCE and TCE is an inducible process. In PCE-limited chemostat cultures of strain TCE1, dechlorination is strongly inhibited by sulfite but not by other alternative electron acceptors, such as fumarate or nitrate.